The Attractiveness of Using Cryptocurrency - Nasir, M.; Saputro, Edy Purwo; Nugroho, Sidiq Permono; Setyaningrum, Dewi Probowati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Cryptocurrency is one of the most interesting digital assets to study. The purpose of this research is to find out the attractiveness of using cryptocurrency by involving 150 respondents represented by the millennial generation. The results of the analysis show that the social influence and perceived risk variables affect the intention to adopt cryptocurrency, while the performance expectancy variable has no effect. The limitations of this research serve as a reference for further research related to the intention to adopt cryptocurrencies